Comparative analysis of mitochondrial genomes of Epimedium L. reveals heterogeneity in structure, synteny, intercellular gene transfer, and RNA editing - Xu, De; Huang, Juan; Ma, Qianqian; Wang, Tao; Zhang, Zheming; Wang, Qiang; Wang, Zhide; Xie, Zhou; Liu, Xue; Fu, Liang (Frontiers in Plant Science, 2025)
Epimedium L. is a taxonomically complex genus comprising 68 species worldwide, yet its mitochondrial genome (mitogenome) remains unexplored. The complete genomes of Epimedium pubescens, Epimedium wushanense, and Epimedium sagittatum were assembled using Illumina and Nanopore sequencing. The Epimedium mitogenomes displayed diverse structural variation, including a single circular molecule in E. sagittatum (324,345 bp), two circular molecules in E. wushanense (281,026 and 72,800 bp), and a multipartite structure with three circular chromosomes (171,784, 76,915, and 71,519 bp) and one linear chromosome (26,149 bp) in E. pubescens. Each species contained 58 unique genes, including 36 protein-coding genes (PCGs), 19 transfer RNAs (tRNAs), three ribosomal RNAs (rRNAs), and abundant repetitive elements [77–89 simple sequence repeats (SSRs) and 169–380 dispersed repeats]. A total of 642 cytidine (C)-to-uridine (U) RNA editing sites were predicted across 35–36 PCGs, with experimentally validated edits generating start and stop codons, revealing species-specific editing profiles. Nine mitochondrial plastid DNA (MTPT) fragments (4.4–7.5 kb) were identified per species, containing six to nine complete genes. Three Epimedium species and related taxa exhibited conserved mitogenome regions alongside extensive gene rearrangements and inversions. Phylogenetic analysis based on 29 conserved PCGs strongly supported a monophyletic Epimedium clade (100% bootstrap), with E. sagittatum and E. pubescens forming a sister group to E. wushanense. This study provides the first comprehensive view of Epimedium mitogenome architecture, RNA editing, and evolutionary relationships, enriching our understanding of its mitochondrial evolution and taxonomy.